2015
DOI: 10.5114/pwki.2015.52289
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic infrarenal abdominal aortic pseudoaneurysm treated with bifurcated endovascular graft stent

Abstract: Posttraumatic infrarenal aortic pseudoaneurysms are rare and potentially lethal lesions. We report the case of a 32-year-old man presenting with infrarenal aortic pseudoaneurysm eight months after being stabbed in the back and right flank. His pseudoaneurysm was close to the iliac bifurcation, so we decided to deploy a bifurcated endovascular graft stent, the TriVascular Ovation endovascular stent. Imaging one month after the procedure revealed no endoleak and slight shrinkage of the pseudoaneurysm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Looking back upon this case, this 83-year-old patient may have been a good candidate for EVAR. In addition, a case of ruptured aortic PA near the aortic bifurcation that was treated successfully with EVAR has been reported [19]. However, we could not completely dismiss the possibility of a mass lesion originating from bowel or mesentery; thus, open surgery with graft interposition was performed after exploration.…”
Section: Discussionmentioning
confidence: 97%
“…Looking back upon this case, this 83-year-old patient may have been a good candidate for EVAR. In addition, a case of ruptured aortic PA near the aortic bifurcation that was treated successfully with EVAR has been reported [19]. However, we could not completely dismiss the possibility of a mass lesion originating from bowel or mesentery; thus, open surgery with graft interposition was performed after exploration.…”
Section: Discussionmentioning
confidence: 97%
“…More recently, Oner et al 10 ) have reported a case of post-traumatic AAP 8 months after being stabbed in the back and right flank. The pseudoaneurysm was close to the iliac bifurcation; the authors decided to deploy a bifurcated endovascular graft stent, the TriVascular Ovation endovascular stent and successfully resolved the case.…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular repair for the treatment of AAP has been reported through the application of stent grafts in two case reports and with a balloon-expandable bifurcated endoprosthesis in other cases. 7 10 )…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, bifurcated stent grafts comprised of modular components that allow graft-guided blood flow to the two iliac arteries are most commonly used in endovascular aneurysm repair (EVAR) [ 1 , 2 ]. The conventional surgery procedure employs proximal neck deployment (with an attached ipsilateral iliac limb) first, followed by contralateral iliac limb deployment.…”
Section: Introductionmentioning
confidence: 99%